Pain prevalence and chronicity in a developing country in Latin America: a population-based survey in Lima, Peru - Leyva, EO (2022)
Background: No population-based epidemiological studies have estimated pain prevalence and its characteristics in Peru. Patients & methods: A representative sample of adults aged over 18 years (n = 502) living in metropolitan Lima, Peru was enrolled. We analyzed prevalence data of pain in the last 3 months and other pain-related characteristics. Results: Pain prevalence was 65.3% (95% CI: 57.7-70.4%). Chronic pain prevalence was 38.5% (95% CI: 33.5-44.0%) and acute pain prevalence was 24.8% (95% CI: 20.7-29.0%). In participants with chronic pain, almost half (55.7%) reported having not used any medication. Conclusion: Pain is prevalent in this population and our results suggest high undertreatment rates. © 2022 The Authors. Plain language summary Although pain is a very important health problem, little is known in Peru about how many people it affects and what its characteristics are. This study aimed to determine the frequency of pain and other related characteristics such as type and location. A sample of inhabitants of metropolitan Lima were surveyed in their homes and were asked about their pain experience in the last 3 months. We found that about seven out of ten had experienced pain in the last 3 months. More than one-third of the participants had pain that lasted more than 3 months (chronic pain). Nearly one-half of the participants with chronic pain had not used any medication to manage their pain. In conclusion, pain is prevalent in the Peruvian population and the results suggest that a large proportion of these people did not receive adequate medical treatment.